If it's not what You are looking for type in the equation solver your own equation and let us solve it.
180=x+(3x+25)+(x-5)x=
We move all terms to the left:
180-(x+(3x+25)+(x-5)x)=0
We calculate terms in parentheses: -(x+(3x+25)+(x-5)x), so:We get rid of parentheses
x+(3x+25)+(x-5)x
We multiply parentheses
x^2+x+(3x+25)-5x
We get rid of parentheses
x^2+x+3x-5x+25
We add all the numbers together, and all the variables
x^2-1x+25
Back to the equation:
-(x^2-1x+25)
-x^2+1x-25+180=0
We add all the numbers together, and all the variables
-1x^2+x+155=0
a = -1; b = 1; c = +155;
Δ = b2-4ac
Δ = 12-4·(-1)·155
Δ = 621
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{621}=\sqrt{9*69}=\sqrt{9}*\sqrt{69}=3\sqrt{69}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-3\sqrt{69}}{2*-1}=\frac{-1-3\sqrt{69}}{-2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+3\sqrt{69}}{2*-1}=\frac{-1+3\sqrt{69}}{-2} $
| 180=x+3x+25+x-5 | | 180=x+(3x+25)+(x-5) | | x=(3x+35)x-5 | | y=34y-19 | | 15x/13-14x=15 | | X=34y-19 | | H=300-15t | | 3(2+x)-2(x-1)=7 | | CxC+C=210 | | 18n+150=402 | | (-8x+91)+(-4x+48)=2(x-6) | | 28-6=n | | 28+6=n | | 12n+14=194 | | x^2-33x+45=0 | | 3-2{9+2m}=m | | 3y+13=112 | | 15x÷13-4x=5 | | x+13+x+25=180 | | x(3x+48)=1260 | | 15x/13-4x=5 | | 2(2x+6)=8x+2 | | 2(4x+6)-6+2(4x+6)-6x=12x-4(x+2) | | 2(4x+6)-6x2(4x+6)-6x=12x-4(x+2) | | 2m+25=3m-5 | | x2+16x=-41 | | 3(x+6)=3(x+6)=48 | | 14+2n=16 | | 10x+9x+9x=248 | | 3x+6-x=30-6 | | 13-8x^2=1139 | | 5(x=43)=2(3x+4) |